Implementation of Elementary and MI Students' Basic Literacy Strengthening Program in East Lombok Regency - Aswasulasikin Aswasulasikin; Suhirman Suhirman; Husnul Mukti; Ahmad Yasar Ramdan; Dina Apriana (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to identify the level of students' reading ability; described the implementation of the basic literacy strengthening program in schools; and described the reflection on basic literacy strengthening programs. This study used descriptive qualitative research, with a target school of 30 SD and MI in East Lombok, and involves supervisors, principals, teachers, and students. Data collection techniques used reading competency assessment, interviews, observation, FGD, and documentation. Data analysis used an interactive model, including data reduction, data presentation, and concluding. The results of the study found that: 1) student literacy at the proficient level was 338, 200 proficient abilities, 217 basic abilities, and 2.067 special interventions; 2) program implementation is divided into the stages of preparation and capacity building, collaboration, and active participation; 3) the results of program reflection show that there are 21 schools with an optimal score, 7 schools with a targeted score, and 2 schools with a score just starting. The reflection process is very important to review the achievements made by the school and the things that need to be improved from various aspects.